Health effects of UV nail lamps - is there a risk of cancer? - Katarzyna Basta-Arciszewska; Kamil Arciszewski; Joanna Borowik; Wojciech Brodowski; Aleksandra Swora; Oliwer Sygacz; Piotr Pawłowski; Przemysław Żelazny; Joanna Filipczak; Sara Dankiewicz; Sebastian Bróż (Kazimierz Wielki University, 2022)
Introduction:  Every year, more and more people are using manicure and pedicure services performed with UV lamps. As public awareness of the harmfulness of prolonged exposure to UV light increases, there are doubts about the safety of frequent treatments using it. Aim of the study:  The aim of the study was to find out whether regular use of UV nail lamps is safe and to educate patients about the prevention of potential cancer.  Methods and materials:  A literature review was performed in the PubMed database using the keywords: UV; nail lamp; skin cancer; risk. Resulsts:  Certain clinical cases indicate that long-term, regular exposure to UVA radiation from nail lamps can increase the risk of squamous cell carcinoma of the skin and actinic keratosis, but other risk factors may overlap. According to a statement by the U.S. Food and Drug Administration (FDA), the use of these devices is safe. Thus, the results of the studies appear to be inconclusive. Both the researchers who prove the safety of lamp use and those who question it unanimously recommend the use of prophylaxis and educating patients about it. Conclusions:  The use of UV nail lamps is not associated with significant risks. Single clinical cases describing the development of squamous cell carcinoma of the skin and actinic keratosis appear to be anecdotal. As the low probability of cancer formation is still taken into account, it is worth taking the recommended precautions: using creams with a broad-spectrum UV filter 20 minutes before exposure or manicure gloves. Using LED nail lamps instead of classic UV lamps will also be beneficial. The topic is a developing one and will require more research attention.